ROLE OF HERPESVIRUS INFECTION IN SJЦ GREN'S DISEASE - V I Kozina; R M Balabanova; O N Egorova; N P Kosyakova; V I Kozina; R M Balabanova; O N Yegorova; N P Kosyakova (Современная ревматология)
The etiology of Sjц gren's disease (syndrome) - SD, SS - is unknown; however, its frequent development in patients with hepatitis B or C or AIDS in infection with human lymphotropic virus type (HLTV-1) suggests the viral nature of the disease. A large body of data available in the literature shows the promise of studying the implication of viral infection in the development of SD and SS, at the early stages of the development in particular.